(3VhGHW heTQhYjI LQGMI GdJLejd hGdeSDhdjI GdeOfjI GdfGTFI YfgG (B: s (3OQGSI ebGQfI (B/ s - (3eMeO Ydi eMeO SGde GdSeQi s; (3fRjg eMeO GdUGOb GdegOi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JYJHQ LQGMI GdJLejd ef GMOK eLGdGJ GdLQGMI GdMOjKI GdJi de JSJbQ GMcGegG GdfXQjI Gh GdhVYjI Gh GdbVGFjI GSJbQGQG cGedG hde Jdb JfXjeG JTQjYjG hVYjG jYGdLgG ShGA ef MjK JMOjO GMcGegG Gh ef MjK JMOjO NUhUjGJ eSFhdjI LQGM GdJLejd HTGfgG hGJHY GdHGMK ai gPI GdOQGSI GdefgL GdhUai GdJMdjdi hGdefgL GdebGQf hOGQJ GdOQGSI Mhd GdebUhO HLQGMI GdJLejd hGdCSS GdJi Jbhe YdjgG hGdJRGeGJ GdWHjH GdNGUI ai LQGMI GdJLejd hWHjYI eSFhdjI LQGM GdJLejds
The plastic surgery of the newest areas of modern surgery that did not settle the provisions of the theoretical or legal status or fully stable, and did not receive a legislative organization and Daaa addressed, both in terms of defining its terms, or in terms of identifying the specificities responsible plastic surgeon about it. And follow the researcher in this study, descriptive analytical method, and the comparative method. Came to study in the first three chapters: the intended cosmetic surgery and the foundations upon which the. Second, the obligations of a physician in private plastic surgery. Chapter III the nature of the responsibility of a plastic surgeon. And the researcher to a number of recommendations, to cause the obligations of modern doctor legislation Arab governing the Medical Responsibility Like delegated to the UAE, who enter these commitments by Federal Law No. (10) for the year 2008 for responsibility Semi-Medical, and put the medical profession rules and provisions for showing the responsibility of doctors for their actions, take into account the nature of their work and their risks, so as to determine the nature of medical errors, taking into account that enjoyed by the profession of a special nature.
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B296-303s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdJHUjQ GdhGLH ddeQjVs; (3GdGdJRGe HGdGOdGA h GdGaUGMs; (3LQGMI GdJLejd s; (3egfI GdWHs; (3GdMUhd Ydj QVGA GdeQjVs; (3YedjGJ fbd GdOes; (3GdNWC GdWHjs; (3GdGLgRI h GdGOhGJ GdWHjIs; (3GdeSFhdjI GdJbUjQjIs; (3LQGM GdJLejds; (3GdOhGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs